Research on the Impact of Regional Economy on Industrial Development from the Perspective of Big Data - Lu Zhang; Dong Zhao; Siheng Li; Han Xiao; Jianjun Bu; Marvin White (Applied Bionics and Biomechanics)
In order to study the driving force of China’s rapid economic development in the past ten years, the study takes Guizhou, Yunnan, and Guangxi as a case study, focusing on the big data assets exchange (GBDEx) and Beibu Gulf Economic Zone, and discusses the impact of Internet plus economic and government data and the big data system on regional economy. Finally, it is believed that the Internet and big data fully avoid the disadvantages of traffic distance between the western region and the eastern region, make full and efficient cooperation between enterprises and institutions in the central and western regions and Chinese and foreign economic entities, and strengthen the control of economic behavior from the big data level with the support of the service-oriented government. The information entropy output from the Internet big data system has led to a significant entropy reduction process in China’s economic environment and a more orderly economic system, which is also an important reason for the rapid development of China’s economy.